Body Mass Index and Waist Hip Ratio as a Risk Factor for Meningioma Incidence - Yuniarti, Heny; Subagio, Hertanto W.; Puruhita, Niken; Murbawani, Etisa A.; Nugrohowati, Annta K.; Priambada, Dody; Risdianto, Ajid (Current Nutrition & Food Science, 2021)
Background: Meningioma is a pathological condition in the central nervous system (CNS), while obesity is defined as excess fat accumulation in the body, which is associated with adverse effects on health. Obesity is characterized by an increase in the Body Mass Index (BMI) and Waist Hip Ratio (WHR). Research on the relationship of BMI, and WHR with meningioma has been widely carried out in various countries of Europe, however, it has not been done much in the Asian countries, especially in Indonesia. Objective: To prove BMI and WHR as risk factors for the incidence of meningioma after being controlled by confounding variables of age and sex. Methods: This is a case-control research involving 44 meningioma patients and 44 family members as controls. The study was conducted at the outpatient clinic at Kariadi Doctors Hospital from May 2019 to June 2019. We collected data including age, sex, BMI, and WHR. Bivariate analysis using the Chi-square test and multivariate analysis with logistic regression was performed. Results: Bivariate test results showed a significant relationship between meningioma and BMI (p < 0.001), WHR (p < 0.001), and sex (p < 0.001). Multivariate test results found that the variables that influence the incidence of meningioma the most were BMI, WHR, and sex. Conclusion: Besides BMI, the increase of WHR and female sex are risk factors for meningioma incidence.
Keywords: Meningioma